Iron‐Based Fischer‐Tropsch Catalysts for Higher Alcohol Synthesis. Issue 5 (1st March 2018) - Schaller, Max; Reichelt, Erik; Jahn, Matthias
Abstract: A short overview over state‐of‐the‐art synthesis routes to higher alcohols from syngas is given. The literature shows that iron‐based catalysts offer the potential for higher alcohol production but cannot fully compete with catalyst systems based on molybdenum and cobalt so far. However, the results presented in this short communication show that by proper choice of reaction conditions and promotion of the catalysts a promising selectivity to higher alcohols and other oxygenates can also be reached for low‐priced iron‐based catalysts. Abstract : A short literature overview on the synthesis of higher alcohol is given. First experimental results are presented showing that with iron‐based catalysts a high selectivity to alcohols with chain lengths C≥3 can be achieved.